Effect of oral anticoagulant use on surgical delay and mortality in hip fracture: a systematic review and meta-analysis. (1st February 2021) - You, Daniel; Xu, Yan; Ponich, Brett; Ronksley, Paul; Skeith, Leslie; Korley, Robert; Carrier, Marc; Schneider, Prism S.
Abstract : Aims: Current guidelines recommend surgery within 48 hours among patients presenting with hip fractures; however, optimal surgical timing for patients on oral anticoagulants (OACs) remains unclear. Individual studies are limited by small sample sizes and heterogeneous outcomes. The aim of this study was to conduct a systematic review and meta-analysis to summarize the effect of pre-injury OACs on time-to-surgery (TTS) and all-cause mortality among older adults with hip fracture treated surgically. Methods: We searched MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception to 14 October 2019 to identify studies directly comparing outcomes among hip fracture patients receiving direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs) prior to hospital admission to hip fracture patients not on OACs. Random effects meta-analyses were used to pool all outcomes (TTS, in-hospital mortality, and 30-day mortality). Results: A total of 34 studies (involving 39, 446 patients) were included in our systematic review. TTS was 13.7 hours longer (95% confidence interval (CI) 9.8 to 17.5; p < 0.001) among hip fracture patients on OACs compared to those not on OACs. This translated to a three-fold higher odds of having surgery beyond the recommended 48 hours from admission (odds ratio (OR) 3.0 (95% CI 2.1 to 4.3); p = 0.001). In-hospital mortality was higher (OR 1.4 (95% CI 1.0 to 1.8); p < 0.03) among anticoagulated patients. Among studies comparing anticoagulants, there was no statistically significant difference in time-to-surgery between patients taking a DOAC compared to a VKA. Conclusion: Patients presenting with a hip fracture who were taking OACs prior to injury experience a delay in time-to-surgery and higher mortality than non-anticoagulated patients. Patients on DOACs may be at risk of further delays. Evaluating expedited surgical protocols in hip fracture patients on OACs is an urgent priority, with the potential to decrease morbidity and mortality in this group of high-risk patients. Cite this article: Bone Joint J 2021;103-B(2):222–233.